2011
DOI: 10.1155/2011/795047
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trail Comparing the Efficacy of 0.5% Centbucridine to 2% Lignocaine as Local Anesthetics in Dental Extractions

Abstract: The development of local anesthesia in dentistry has marked the beginning of a new era in terms of pain control. Lignocaine is the most commonly used local anesthetic (LA) agent even though it has a vasodilative effect and needs to be combined with adrenaline. Centbucridine is a non-ester, non amide group LA and has not been comprehensively studied in the dental setting and the objective was to compare it to Lignocaine. This was a randomized study comparing the onset time, duration, depth and cardiovascular pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Three prospective studies were included in this study (Dugal et In first study the patient received 3 ml of anesthetic for nerve blocks using either 0.5% Centbucridine HCI or 2% Lignocaine HCI with adrenaline (1:200,000) (Dugal et al, 2009). In the second study patients randomly received a single anesthetic dose of either 0.5% Centbucridine HCI or 2% Lignocaine HCI with adrenaline (1:200,000) (Mansuri et al, 2011). In last study both drugs were supplied in equal amounts in identical vials labeled only with a code number (Goyal et al ., 2013).…”
Section: Results:-mentioning
confidence: 99%
See 2 more Smart Citations
“…Three prospective studies were included in this study (Dugal et In first study the patient received 3 ml of anesthetic for nerve blocks using either 0.5% Centbucridine HCI or 2% Lignocaine HCI with adrenaline (1:200,000) (Dugal et al, 2009). In the second study patients randomly received a single anesthetic dose of either 0.5% Centbucridine HCI or 2% Lignocaine HCI with adrenaline (1:200,000) (Mansuri et al, 2011). In last study both drugs were supplied in equal amounts in identical vials labeled only with a code number (Goyal et al ., 2013).…”
Section: Results:-mentioning
confidence: 99%
“…The use of adrenaline as a vasoconstrictor is sometimes contraindicated for medically compromised patients. To overcome these disadvantages, other local anesthetics have been developed over the past few years (Dugal et al, 2009;Mansuri et al, 2011 ;Goyal et al ., 2013).…”
Section: Int J Adv Res 5(3) 1833-1844mentioning
confidence: 99%
See 1 more Smart Citation
“…Centbucridine has been investigated for infiltration, conjunctival surface, in peripheral nerves, neuroaxial anesthesia, intravenous regional anesthesia; however, the majority of studies are in dental anesthesia [9,[50][51][52]. Most studies compare 0.5% centbucridine vs. 2% lidocaine, with similar anesthetic results, although some have found longer anesthetic duration in patients who were treated with centbucridine [51,53]. Centbucridine can be used with confidence in dental patients who cannot tolerate other LAs or when epinephrine is contraindicated.…”
Section: Centbucridinementioning
confidence: 99%
“…2 Samir Mansuri et al, compared the efficacy of 0.5% centbucridine to 2% lignocaine and concluded that centbucridine has inherent vasoconstrictor ability. 1 As centbucridine has inherent vasoconstriction ability it can be used without addition of vasoconstrictor, while lignocaine is used with 1:200,000 adrenaline to nullify its inherent vasodilating property. Dugal et al, did a comparative study between 0.5% centbucridine HCl and 2% lignocaine HCl with adrenaline (1:200,000).…”
Section: 19mentioning
confidence: 99%